The Role of Chitinase 3-Like-1 (YKL-40) and Proinflammatory Biomarkers in the Pathogenesis of Pediatric Tick-Borne Encephalitis in a Polish Cohort - Bojkiewicz E; Toczylowski K; Lewandowski D; Martonik D; Flisiak R; Sulik A (Journal of Inflammation Research)
Ewa Bojkiewicz,1 Kacper Toczylowski,1 Dawid Lewandowski,1 Diana Martonik,2 Robert Flisiak,2 Artur Sulik1 1Department of Pediatric Infectious Diseases, Medical University of Bialystok, Bialystok, Poland; 2Department of Infectious Diseases and Hepatology, Medical University of Bialystok, Bialystok, PolandCorrespondence: Kacper Toczylowski, Email kacper.toczylowski@umb.edu.plBackground: Chitinase 3-like-1 (CHI3L1), also known as YKL-40, is a potential biomarker for neuroinflammatory conditions. It is upregulated in Alzheimer’s disease, multiple sclerosis, and traumatic brain injury. However, its involvement in pediatric tick-borne encephalitis (TBE) has not been addressed yet. This study aimed to evaluate CHI3L1 and its relationship with other inflammatory cytokines, blood-brain barrier (BBB) integrity, immune response, and disease severity in pediatric patients with TBE.Patients and Methods: A total of 22 pediatric TBE patients hospitalized in Bialystok, Poland were included in this study. Participants were categorized as having meningoencephalitis (n=6) or meningitis (n=16). The integrity of the brain-blood barrier (BBB) was assessed using the albumin quotient (albQ). Biomarker indices were calculated to account for variations in BBB permeability. The concentrations of CHI3L1, CCL2, chemerin, CXCL2, IFN-γ, IL-1-β, IL-4, IL-6, IL-13, and TNF-α in both serum and CSF, were measured using the Luminex Multiplex Assay od admission and two weeks later when symptoms resolved.Results: CSF and serum concentrations of CHI3L1 did not differ between the encephalitis and meningitis cases. After adjusting for BBB permeability, the CHI3L1 index was 2.4-fold lower in patients with encephalitis than in those with meningitis (P=0.008). There was a post-treatment reduction of CHI3L1, IL-6, and TNF-α CSF concentrations. We also found and improvement in BBB permeability in younger children but in older albQ remained abnormal. Correlation analysis revealed associations between CHI3L1 levels and pro-inflammatory markers, notably chemerin, IL-6, and TNF-α, across both clinical groups.Conclusion: Our findings suggest that CHI3L1 CSF levels reflect the inflammatory activity in pediatric TBE and may help to differentiate between meningoencephalitis and meningitis. The observed interactions between CHI3L1 and other cytokines underscore its potential involvement in inflammatory response to the virus. The prolonged disruption in BBB integrity in older children might reflect age-dependent differences in the severity of TBE. These insights advance our understanding of TBE pathogenesis in children and support further investigation of CHI3L1 as a biomarker for TBE diagnosis and management.Keywords: chitinase-3-like-1, tick-borne encephalitis, blood-brain barrier, ticks, chemokines